[11C]PiB and [18F]AV45 PET radiotracers show different rates of amyloid‐β clearance. (31st December 2021) - Chen, Charles D.; McCullough, Austin A.; Gordon, Brian A.; Joseph‐Mathurin, Nelly; Wang, Guoqiao; Li, Yan; Xiong, Chengjie; Pontecorvo, Michael J.; Klein, Gregory; Shcherbinin, Sergey; Higgins, Ixavier A.; Masters, Colin L; et al.
Abstract: Background: Results from the first Dominantly Inherited Alzheimer Network Trials Unit (DIAN‐TU) clinical trial showed Gantenerumab reduces amyloid‐β deposition in autosomal dominant Alzheimer disease individuals. However, it is uncertain whether these initial findings from [11C]PiB PET generalize to other amyloid‐β PET radiotracers. Method: We acquired [11C]PiB and [18F]AV45 PET in mutation positive DIAN‐TU participants in the gantenerumab ( n =30) and placebo drug arms ( n =19). Participants were assessed at baseline and Year 4; at each visit, [11C]PiB and [18F]AV45 PET were acquired, with at most 28 days between imaging sessions. Regional standardized uptake value ratios (SUVRs) were quantified using the PET Unified Pipeline. Annualized SUVR percent change between baseline and Year 4 for both radiotracers in both drug arms were calculated. Differences in SUVR change between radiotracers/drug arms were assessed using the Wilcoxon signed‐rank/rank‐sum test. Each test statistic is reported as a rank‐biserial correlation r accompanied by p ‐values adjusted for false discovery control by the Benjamini‐Hochberg procedure at level q =0.20. Result: We observed a decrease from baseline to Year 4 SUVR in the gantenerumab arm, which was larger when studied with [11C]PiB than with [18F]AV45 PET in several regions, including the striatum and cingulate gyrus ( r =[‐0.79, ‐0.31], FDR‐adjusted p ‐values=[0.00086, 0.19], Figure 1). In contrast, we observed an increase in SUVR in the placebo arm, comparable in magnitude between [11C]PiB and [18F]AV45 PET ( r =[‐0.15, 0.68], FDR‐adjusted p ‐values=[0.29, 0.86]). Conclusion: Differences seen between the effects of gantenerumab in [11C]PiB versus [18F]AV45 PET suggest several regions, such as the striatum and cingulate gyrus, may be inappropriate for radiotracer harmonization in studies involving gantenerumab. More practically, the finding that anti‐amyloid‐β therapies may have different effects on signal across radiotracers suggests multi‐site studies of anti‐amyloid‐β treatments should agree on a single radiotracer for best results. Follow‐up postmortem studies will be conducted to determine the binding affinity of various amyloid‐β radiotracers to amyloid‐β plaques in this cohort.